COMPARISON OF VARIATIONS OF ROBUSTA AND ARABIKA COFFEE GROUNDS BY COMPOSITION (60%: 40%, 50%: 50%, 40%: 60%) TO DETERMINE THE HARDNESS AND CALORIFIC VALUE OF BRICKETS - Aprilliano , Francisko; Tugur Redationo, Nereus; Cristanto Putra Mbulu, Bernardus (Universitas Katolik Widya Karya Malang, 2025)
Along with the times, the availability of fossil energy is decreasing, especially natural gas and coal, before using fossil energy, humans have used biomass as an energy source. Indonesia has many plantation commodities, one of which is coffee which is the fourth largest coffee producer in the world. Coffee grounds are the main waste produced by coffee shops and are usually only thrown away. The main ingredients in this study were arabica coffee grounds and robusta. By using robusta composition 60% arabica 40%, robusta 50% arabica 50% robusta 40% arabica 60%. In addition, briquettes are tested for hardness by making points on the surface of the briquettes using a durometer shore A tool of 30 points, then a calorimeter bomb test is carried out to obtain the calorific value content. The result obtained from the highest hardness value is briquettes with a robusta mixture of 50% arabica 50% with a value of 23.7 HA, while the highest calorific value is found in a robusta mixture of 60% arabica 40% with a value of 4526.85 cal / gram.